MOTIVASI KERJA APARATUR SIPIL NEGARA DALAM MENINGKATKAN KINERJA DI DINAS KETAHANAN PANGAN KABUPATEN PASANGKAYU - Misda W; Nawawi Natsir; Dandan Haryono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this research is to determine the work motivation of state civil servants in improving performance at the Pasangkayu Regency Food Security Service, which was studied based on the work motivation theory model according to David Mc Clelland (Siagian, 2004: 167). 1). The need for achievement, 2). The need for power, 3). The need for affiliation, the type of research used is descriptive qualitative with purposive selection of informants and the number of selected informants is 5 people using data collection techniques, 1). Observation, 2). Interview, 3) Documentation. By analyzing all the interview results. The data was analyzed using several steps according to the theory of Miles, Huberman and Saldana (2014), namely analyzing the data in three steps: data condensation, presenting the data (data display), and drawing conclusions or verification (conclusion drawing and verification). The results of research on work motivation for state civil servants in improving performance at the Pasangkayu Regency Food Security Service showed that the need for achievement requires the work enthusiasm of officials to develop creativity and direct all their abilities in order to achieve work performance, so it is necessary to increase abilities both technically, conceptually and human relations. Meanwhile, the research results were obtained from the need for power, the work spirit of an employee so that he mobilizes all his abilities in order to achieve the best power/position in the organization, with the hope of being promoted to occupy a position. And the need for affiliation has the desire to create and maintain friendship and warm relationships with other people. Collaboration between teams also continues to be improved. Overall, employee work motivation can be said to be good, but it needs to be improved further so that the Vision and Mission of the Food Security Service can be achieved.